6(z+3)+9=27.

Simple and best practice solution for 6(z+3)+9=27. equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(z+3)+9=27. equation:



6(z+3)+9=27.
We move all terms to the left:
6(z+3)+9-(27.)=0
We add all the numbers together, and all the variables
6(z+3)+9-27=0
We add all the numbers together, and all the variables
6(z+3)-18=0
We multiply parentheses
6z+18-18=0
We add all the numbers together, and all the variables
6z=0
z=0/6
z=0

See similar equations:

| w-1.96=9.4 | | x+2=-101 | | 20+3y/5=20 | | 3(k+2)=15k= | | 3(k+2)=15k | | |2r+3|-10=0 | | k^2-4k-45=15 | | |x-2|+9=7 | | 23=y5-14 | | -24=-13f+15 | | 10=12+-1w | | 5-4x+10=x+2x-5 | | 12x-9=-105 | | (4y-45)°=7 | | 35=8c+3 | | 8y+4=10+10y | | 150=-5x+7(7x-15) | | -20+5x=65 | | (5/9)(f-32)=-20 | | -24=-8y+4(y+5) | | 7^4x-7^(2x+1)=8 | | (f-32)*(5/9)=-20 | | 6x+14=-x+77 | | (5(3w+8))/3=9 | | -2x-3(-4)=48 | | 9(u-9)=36 | | 2(q-4)=18 | | 2(q-4)=118 | | x^2-12x-320=0 | | −40+10a=  −70−70 | | 2(2x-3)-2x=-18 | | 2(-2x-3)=-18 |

Equations solver categories